Social Consequences of Car Accident in Kurdistan - Suren Akram Hamanajm (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
All scientific research is conducted with the aim and purpose, our goal in this research is to show the consequences of car accidents in Kurdistan. This research has two gates, the first gate is dedicated to the theory of the research and it has three chapters. In chapter one, a research problem, a research significance, a research purpose has been written as well as the concept of (Consequence, car accident, Erbil) has been defined. In chapter two the map of Erbil’s rood and the history of police traffic in Erbil has been written in another. on chapter three the reasons for car accidents and the statistics of the Erbil traffic directorates have been analyzed. The second gate has been dedicated to applied research and it has the community of the Research, the sample of the research, the method of the Research, the Areas of the research and Tools for Gathering Information, Tools statistical of Data analysis as well. Chapter five is about Analysis and Presentation Data, first debate shows Analysis and Presentation Data, Second debate determinations Conclusion, Research results, Research recommendations Research suggestions, Bibliography, Appendix.